Low-pressure long-time or moderate pressure pasteurization at room temperature by hyperbaric inactivation as a new nonthermal preservation approach – A case study on milk. (August 2022) - Lemos, Álvaro T.; Martins, Ana P.; Delgadillo, Ivonne; Saraiva, Jorge A.
Abstract: A new nonthermal food pasteurization approach is here presented for the first time, proposed to be called low-pressure long-time (LPLT) pasteurization or moderate pressure pasteurization (MPP) by hyperbaric inactivation (HI). To test this novel pasteurization process on raw milk, MPP by HI was carried out at three different pressure levels (150, 200 and 250 MPa), over 24 h, at naturally variable uncontrolled room temperature (≈20 °C) and compared with high pressure processing (HPP) at 600 MPa (one cycle for 90 s and a second cycle of 120 s) followed by storage under refrigeration for 21 days. Based on the results obtained, MPP at 250 MPa over 24 h caused higher microbial inactivation on total aerobic mesophiles (TAM), lactic acid bacteria (LAB) and Enterobacteriaceae (ENT) (of at least 2.2, 1.7 and 1.3 log CFU/mL, respectively) than HPP (1.1, 1.0 and 1.2 log CFU/mL, for the same microorganisms). Moreover, MPP showed a clear reduction of inoculated microorganisms to below the detection limit, in only 16 h for all pressures with reductions of at least 5.7, 5.4 and 5.5 for Listeria innocua, Salmonella senftenberg, and Escherichia coli, respectively. Additionally, during preservation under refrigeration, MPP samples (200 MPa and 250 MPa), maintained lower TAM/LAB/ENT compared to HPP, being the counts below the quantification/detection limit for at least 21 days for MPP by HI. MPP (200 MPa and 250 MPa) resulted also in counts below the detection limit for the inoculated microorganisms up to at least 21 days under refrigeration. The results of MPP by HI are very promising as a new nonthermal food pasteurization, since over 5 log reduction of vegetative bacteria were achieved, with counts maintained below the quantification/detection limit for at least 21 days under refrigeration. Highlights: Moderate pressure pasteurization (MPP) has potential for nonthermal pasteurization. MPP (250 MPa, 24 h) caused higher microbial reduction than HPP (600 MPa, 90 s + 120 s). MPP (200/250 MPa, 12 h) inactivated over 5 log of E. coli / L. innocua / S. senftenberg. MPP (200/250 MPa, 12 h) inactivated 2 log of lactic acid bacteria. After MPP microbial loads were maintained at least for 21 days under refrigeration.